2008
DOI: 10.1080/03601230801941634
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pesticide residues in IPM and non-IPM samples of mango (Mangifera indica)

Abstract: Studies were conducted to analyze the residue of commonly used pesticides viz. methyl parathion, chloropyrifos, endosulfan, cypermethrin, fenvalerate, carbendazim, imidacloprid and carbaryl in mango, Dashehari variety, integrated pest management (IPM) and non-IPM samples were collected from the IPM and non-IPM orchards, Lucknow, India. We also present a method for the simultaneous determination of these pesticides in mango samples. Residues of methyl parathion, chloropyriphos, endosulfan, cypermethrin, fenvale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In our earlier studies, it was found that acetone and acetonitrile extracted a large amount of undesirable polar coextractives, and recoveries were around 70-78% for GC compatible pesticides (19). A modified extraction was standardized (acetone:cyclohexane:ethyl acetate in the ratio 2:1:1) to analyze the IPM and non-IPM mango samples, and good recovery was obtained (20). The same method was tried for six pesticides in the case of apple samples, and no interfering peaks were found in the fortified samples (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier studies, it was found that acetone and acetonitrile extracted a large amount of undesirable polar coextractives, and recoveries were around 70-78% for GC compatible pesticides (19). A modified extraction was standardized (acetone:cyclohexane:ethyl acetate in the ratio 2:1:1) to analyze the IPM and non-IPM mango samples, and good recovery was obtained (20). The same method was tried for six pesticides in the case of apple samples, and no interfering peaks were found in the fortified samples (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Integrated pest management (IPM) has been adopted to maximize crop yield while maintaining a quality environment with regard to pesticide contamination, solving ecological problems and contributing to the sustainability of agriculture. 1 These preventive practices were preceded by other actions. For instance, OCP have been banned since the 1970s because they are extremely persistent in the environment and due to their ability to accumulate in sediments, plants, and animals.…”
Section: ' Introductionmentioning
confidence: 99%
“…Despite the usefulness of pesticides in agricultural practices, there are concerns about their excessive use and their presence and levels in the environment and foodstuffs. Integrated pest management (IPM) has been adopted to maximize crop yield while maintaining a quality environment with regard to pesticide contamination, solving ecological problems and contributing to the sustainability of agriculture . These preventive practices were preceded by other actions.…”
Section: Introductionmentioning
confidence: 99%
“…This vitamin helps to improve immunity and to protect common infections and pathogens 2 . However, due to high temperature and high humidity in the tropical region mango is infested by more than 492 species of insects, 17 species of mites and 26 species of nematodes 3 …”
Section: Introductionmentioning
confidence: 99%